International Finance Corporation Additionality in Middle-Income Countries : Approach Paper - Independent Evaluation Group (Washington, DC : World Bank, 2022)
Accounting for almost half of global gross domestic product and 70 percent of the world’s population, middle-income countries (MICs) face multiple development challenges limiting achievement of the Sustainable Development Goals (SDGs), including poverty and inclusion, climate change, financial access, and economic diversification and market development. The International Finance Corporation’s (IFC) portfolio is focused heavily on MICs. Additionality is the unique support that IFC brings to a private client or client country that is not typically offered by commercial sources of finance (IFC 2019). This evaluation assesses the unique support and value addition (additionality) that the International Finance Corporation (IFC) provides to middle-income countries (MICs). It will cover IFC’s support of MICs through investment and advisory projects, and through its platforms and partnerships. The primary audience is the World Bank Group Board and IFC management and staff, however some findings of the evaluation will be relevant to a broader audience including multilateral and bilateral financing private sector activities, investors, and government officials and practitioners in client countries.